A Framework for Component Design using MVC Design Pattern - Sengupta, Abhik; Sengupta, Sabnam; Bhattacharya, Swapan (INFOCOMP Journal of Computer Science, 2008)
In this paper, we propose a framework where functional requirements are traced from use case model to component model via analysis and design models. Here, components of the component models are derived by grouping and packaging design classes based on the type of analysis classes they are derived from. As there are three different types of analysis classes: boundary, controller and entity, the design classes derived from the corresponding analysis classes get classified at the first iteration. The components thus derived using this approach form the components of Model View Controller Architecture; different components having design classes of similar functionalities. This framework can be used to verify and ensure that use case flow of events is traced in analysis model and then to component model via design models. The architecture with the components designed using this framework also ensures separation of concerns, roles among the components to achieve high cohesion and low coupling